Strategies for the Facilitation of Self-Leadership Among Ward Nurses in a Nurse-Led Critical Care Outreach Service - Carine Prinsloo PhD (SAGE Open Nursing, 2023)
Introduction Nurses are responsible for monitoring and providing nursing care to patients. The early detection of a patient who is starting to deteriorate – and the activation of critical care outreach services (CCOS) – can improve patient outcomes. However, the literature indicates that CCOS are underutilised. Self-leadership is a process whereby persons influence their own behaviour. Objective The purpose of this study was to develop strategies for the facilitation of self-leadership in ward nurses that will enable them to act proactively and promptly in utilising CCOS at a private hospital group in South Africa. Methods A sequential exploratory mixed-method research approach was followed to develop strategies for the facilitation of self-leadership in nurses that will enable them to utilise CCOS proactively when a patient starts to deteriorate. An adapted version of Neck and Milliman's self-leadership strategic framework was used as the methodological steps of the study. Results The quantitative analysis extracted eight factors, which were used as the departure point to develop strategies for the facilitation of self-leadership among nurses in a CCOS. Five strategies were developed that related to self-motivation, role models, patient outcome, assistance and guidance from CCOS, and the power of self-confirmation; these strategies aligned with the themes and categories extracted from the qualitative data analysis. Conclusion There is a need for self-leadership among nurses in a CCOS.